OP0140 DYSREGULATED EXPRESSION OF THE LONG NON-CODING RNA, LINC01871, IMPLICATED IN SJÖGREN'S SYNDROME PATHOGENESIS. (2nd June 2020) - Joachims, M. L.; Khatri, B.; Tessneer, K. L.; Stolarczyk, A. M.; Wiley, G. B.; Rasmussen, A.; Guthridge, J.; James, J. A.; Scofield, R. H.; Sivils, K. L.; Adrianto, I.; Lessard, C.
Abstract : Background: Sjögren's syndrome (SS) is a chronic, heterogenous autoimmune disease characterized by inflammatory destruction of the exocrine glands. Long non-coding RNAs (lncRNAs) have emerged as a functionally diverse class of non-protein coding RNA (ncRNA) with increasing implications in interferon signaling, immune cell regulation, and autoimmune disease pathology. The potential role of lncRNAs in SS pathogenesis is unknown. Objectives: To identify and characterize candidate lncRNAs with potential relevance to SS pathology. Methods: RNA-seq was used on whole blood from SS patients (n=30 antibody negative (Ro - ); n=27 antibody positive (Ro + )) and healthy controls (HC, n=27) to identify differentially expressed (DE) lncRNAs (log2 fold change (FC) ≥ 2 or ≤ 0.5; padj <0.05). Bioinformatic and pathway analyses were used to predict lncRNA function. In vitro time course experiments in HSB2 T cell lymphoblasts stimulated with PMA/Ionomycin (PMA/I) or type I interferon (IFN) were used to assess biological relevance. LINC01871 function was further investigated by RNA-seq on a single cell clone of HSB2 with confirmed CRISPR-targeted LINC01871 deletion ( LINC01871 -/- ). Results: We identified a total of 1054 unique DE ncRNAs between Ro +, Ro - and/or a combined analysis relative to HC; of these, 45 (1 long intergenic ncRNA (lincRNA), 1 antisense, 43 pseudogenes) were overexpressed in all 3 SS subsets. To begin investigating the function of the previously undescribed lincRNA, LINC01871 (SS Ro- : FC=2.85; padj =1.1x10 -4 ), we performed a correlation analysis of the SS Ro- transcriptome, which found several co-expressed protein coding RNAs involved in immune regulation ( THEMIS, TBX21, IL10RA, IL2RB, among many others). Similarly, Ingenuity Pathway Analysis of the SS transcriptome compared to HC, as well as several gene ontology enrichment analyses of publicly available RNA expression correlation databases, identified shared immune-related pathways including cytotoxic T cell, natural killer cell, and T cell regulation. To further study the role of LINC01871 in cytotoxic T cells, we used qRT-PCR to resolve the effects of PMA/I or type I IFN stimulation on LINC01871 expression in the T lymphoblastoid HSB2 cells. LINC01871 expression was downregulated after PMA/I stimulation, but unchanged with type I IFN stimulation. To explore the regulatory function of LINC01871 in T cells, we targeted LINC01871 in HSB2 cells using CRISPR. To this end, we generated a single cell LINC01871 -/- clone with no RNA expression by qPCR and confirmed homozygous deletion using DNA sequencing. RNA-seq analysis of LINC01871 -/- compared to unmodified HSB2 cells identified 1166 DE transcripts. Pathway analyses clustered the DE transcripts into similar immune regulatory, cytotoxic and T cell pathways identified in SS Ro- whole blood RNA-seq and publicly available RNA-seq databases. Further, several prominent T cell regulatory transcripts that exhibited correlated upregulation with LINC01871 in SS Ro- whole blood RNA-seq also demonstrated downregulation after LINC01871 deletion: CD109 (FC=-9.7; padj =5.3x10 -16 ), IL22 (FC=-8.1; padj =7.6x10 -11 ), PDCD1 (FC=-6.2; padj =1.1x10 -6 ), THEMIS (FC=-3.8; padj =2.7x10 -165 ) and TBX21 (FC=-2.1; padj =3.3x10 -25 ). Conclusion: LncRNAs are emerging as important regulators of immune function with increasing evidence of autoimmune disease relevance. Here, we leveraged RNA-seq, extensive bioinformatic data, and CRISPR technology to identify and functionally characterize LINC01871 as a potential mediator of the dysregulated T cell inflammatory response pathways implicated in SS pathogenesis. Disclosure of Interests: Michelle L Joachims: None declared, Bhuwan Khatri: None declared, Kandice L Tessneer: None declared, Anna M Stolarczyk: None declared, Graham B Wiley: None declared, Astrid Rasmussen Speakers bureau: Novartis, ThermoFischer, Joel Guthridge Grant/research support from: Xencor, Bristol Myers Squibb, DXterity, Judith A. James Grant/research support from: Progentec Diagnostics, Inc, Consultant of: Abbvie, Novartis, Jannsen, R Hal Scofield Grant/research support from: Pfizer, Kathy L Sivils: None declared, Indra Adrianto: None declared, Christopher Lessard: None declared